ChemInform Abstract: Microwave‐Assisted One‐Pot Three‐Component Synthesis of Imine 1, 2, 3‐Triazoles. Issue 29 (June 2016) - Souza, Frederico B.; Pimenta, Daniel C.; Stefani, Helio A.
Abstract: Imines, generated in situ from α‐thioaldehydes and propargylamine, undergo cycloaddition reactions with azides to afford novel triazole derivatives.